International collaboration and connections through design thinking: A case study of the Global Classroom for Democracy Innovation (GCDI) - Matthew Wingfield; Jesi Carson; Mukisa Mujulizi; Bettina Von Lieres; Marco Adamovic; Laurence Piper; Wilma Lundqvist Westin (University of Johannesburg, 2024)
This paper is based on the collaborative development of the Global Classroom for Democracy Innovation (GCDI), and its month-long virtual pilot workshop, the 'Climate Change Design Jam'. The GCDI is an integrated learning partnership between three international universities located in Canada, South Africa, and Sweden, and civil society partners the Vancouver Design Nerds (VDN). Each partner brought unique skills to the GCDI, as new processes and methods for virtual, global student engagement and dialogue were co-designed. The GCDI hosted the Climate Change Design Jam over four consecutive weeks in March 2022. By employing a design thinking methodology, it facilitated online student project development around the interconnected and broad topics of climate change and democracy. Students and student facilitators were guided through the process of design thinking to develop grounded projects that address climate change issues locally and internationally. This paper argues that fundamental principles of fostering genuine connections (both 'online' and 'offline') between students can act as a useful foundation from which project development can be based. Further, this paper illustrates that when faced with 'wicked problems' such as climate change and challenges to democracy worldwide design thinking methods and collaborative approaches can act as a catalyst for action (Manzini, 2015). Exploring political theory, democracy, and civic agency through dialogue and co-design provides students with innovative approaches to research, critical thinking, and activism. This pilot series provides insight into student engagement across international contexts, and thus the development of cross-cultural and collective intelligence which can be formative for similar projects in the future (Behari-Leak, 2020).